Healthcare providers' knowledge, attitudes and practices on smoking cessation intervention in the Northern Cape - Lizwe C. Muza; Chika K. Egenasi; Wilhelm J. Steinberg; Mathew O. Benedict; Talat Habib; Ferdinand Mampuya; Cornel van Rooyen (AOSIS, 2024)
Background: Clinicians are crucial in encouraging smokers to quit through behavioural or pharmacological smoking cessation interventions. Smokers quit better with professional help. The level of healthcare providers' (HCPs) knowledge, attitudes and counselling skills related to effective smoking cessation support in the study area remains uncertain. Aim: The study aimed to determine HCPs' knowledge, attitudes and practices (KAP) on smoking cessation intervention strategies in the Sol Plaatje district, Northern Cape. Setting: Sol Plaatje's 13 district municipality clinics, Kimberley, Northern Cape. Method: A descriptive, cross-sectional analytical study involving healthcare workers in the above setting. Results: A total of 165 HCPs, including medical officers, professional nurses, enrolled nurses and assistant-enrolled nurses working in primary healthcare clinics, were invited to participate in the study, with 156 completing the questionnaires. About 53.9% had no knowledge of South African tobacco smoking cessation guidelines, while 87.2% knew the importance of counselling patients about smoking and its impact on quitting. The majority of them did not know the medicines recommended for tobacco treatment in South Africa. About 89.7% expressed that smoking cessation counselling is an important part of their jobs. However, less than half indicated that they make follow-up arrangements for those attempting to quit. Conclusion: The study revealed gaps in KAP regarding smoking cessation among the respondents, necessitating the need for continuing education on the existing smoking cessation guidelines among these HCPs. Contribution: The results of this study will help to improve smoking cessation intervention knowledge among health providers.